Streaming Hallyu, Negotiating Values: Digital Platforms, Social Inequality, and Cultural Reception in Southeast Asia - Darynaufal Mulyaman; Muhammad Ritzky Saibi (MD Research Center, 2026)
The rapid growth of digital streaming platforms has accelerated the circulation of the Korean Wave (Hallyu) across Southeast Asia, yet its reception cannot be understood as a linear process of cultural diffusion. This study aims to examine how cross-border cultural flows are mediated by digital platforms and interpreted within diverse socio-cultural contexts across the region. Employing a qualitative literature review with thematic analysis, the research synthesizes scholarly works on media globalization, streaming platforms, and cultural reception in Southeast Asia. The findings reveal that Hallyu reception is shaped by three interrelated factors: digital infrastructure and platform algorithms that expand access and shape preferences; social inequalities that differentiate consumption patterns across class, education, and geography; and local cultural values, particularly religious norms and identities, that drive processes of adaptation, resistance, and hybridization. Audiences selectively adopt, adapt, or resist cultural elements, producing diverse forms of cultural hybridity that indicate globalization fosters differentiation rather than uniformity. The study concludes that cultural globalization in the digital era is multidimensional, requiring integrated analysis across technological, social, and cultural domains. These findings highlight the importance of strengthening local cultural resilience and offer valuable lessons for developing creative industries capable of competing globally while preserving unique cultural identities in Southeast Asia.